Emergence of Getah Virus Infection in Horse With Fever in China, 2018 - Lu, Gang; Ou, Jiajun; Ji, Jinzhao; Ren, Zixin; Hu, Xue; Wang, Caiying; Li, Shoujun (Frontiers in Microbiology, 2019)
Getah virus (GETV) is a mosquito-borne virus that was first determined in Malaysia in 1955, and can infect humans and multiple other mammals. GETV infection in horses has been reported in Japan and India, and causes great economic losses. In China, GETV has been identified in mosquitoes, pigs, foxes, and cattle with a wide geographical distribution, but has not been detected in horses. In August 2018, a sudden onset of fever was observed in racehorse in an equestrian training center in Guangdong Province in southern China. Blood samples were collected from the sick horse, and PCR/RT-PCR analysis was performed to screen for equine viral pathogens associated with fever. The results indicated that the samples were GETV RNA positive. After RT-PCR, sequencing, and assembly, the genome of the first Chinese horse-derived GETV strain, GZ201808, was obtained. Compared with the genome sequences of other GETV strains, twelve unique nucleotide substitutions were observed in GZ201808. The genome of GZ201808 had the highest genetic identity (99.6%) with AH9192, which was detected in pigs in China in 2017. Phylogenetic analysis indicated that GZ201808 clustered in Group III, and was located in an independent branch distant from other horse-derived GETV strains, indicating a unique evolutionary pattern of GZ201808. This study first determined and described the disease course of horse infected with GETV in China, sequenced and characterized the genome of the field horse-derived GETV strain, and therefore presented an unequivocal report of GETV infection in horses in China.